Spent Yeast Waste Streams as a Sustainable Source of Bioactive Peptides for Skin Applications - Costa, Eduardo M.; Oliveira, Ana Sofia; Silva, Sara; Ribeiro, Alessandra B.; Pereira, Carla F.; Ferreira, Carlos; Casanova, Francisca; Pereira, Joana O.; Freixo, Ricardo; Pintado, Manuela E.; Carvalho, Ana Paula; Ramos, Óscar L. (International journal of molecular sciences, 2023)
Spent yeast waste streams are a byproduct obtained from fermentation process and have been shown to be a rich secondary source of bioactive compounds such as phenolic compounds and peptides. The latter are of particular interest for skin care and cosmetics as they have been shown to be safe and hypoallergenic while simultaneously being able to exert various effects upon the epidermis modulating immune response and targeting skin metabolites, such as collagen production. As the potential of spent yeast’s peptides has been mainly explored for food-related applications, this work sought to understand if peptide fractions previously extracted from fermentation engineered spent yeast (Saccharomyces cerevisiae) waste streams possess biological potential for skin-related applications. To that end, cytotoxic effects on HaCat and HDFa cells and whether they were capable of exerting a positive effect upon the production of skin metabolites relevant for skin health, such as collagen, hyaluronic acid, fibronectin and elastin, were evaluated. The results showed that the peptide fractions assayed were not cytotoxic up to the highest concentration tested (500 µg/mL) for both cell lines tested. Furthermore, all peptide fractions showed a capacity to modulate the various target metabolites production with an overall positive effect being observed for the four fractions over the six selected targets (pro-collagen IαI, hyaluronic acid, fibronectin, cytokeratin-14, elastin, and aquaporin-9). Concerning the evaluated fractions, the overall best performance (Gpep > 1 kDa) was of an average promotion of 41.25% over the six metabolites and two cell lines assessed at a concentration of 100 µg/mL. These results showed that the peptide fractions assayed in this work have potential for future applications in skin-related products at relatively low concentrations, thus providing an alternative solution for one of the fermentation industry’s waste streams and creating a novel and highly valuable bioactive ingredient with encompassing activity to be applied in future skin care formulations.